Allocating an indivisible good. A questionnaire-experimental study of intercultural differences ﻿ - Schokkaert, Erik (2022)
Abstract We present the results of a questionnaire study in Belgium, Burkina Faso and Indonesia focusing on the problem of the just allocation of an indivisible good. The formal axioms proposed in social choice theory offer an attractive framework to structure the response patterns. Interindividual differences can be interpreted in a meaningful way in terms of basic intuitions about desert, efficiency and compensation. Belgian students are most resource-egalitarian, Burkinese students attach a large weight to innate capacities, Indonesian students focus on actual production. The crucial no-envy criterion is supported by a majority of respondents, but this majority becomes small if there is an unavoidable conflict between no-envy and the “responsibility” requirement of the stand-alone upper bound. We discuss the pros and cons of questionnaire-experimental studies as compared to large representative surveys.